Monodromy of an Inhomogeneous Picard-Fuchs Equation - Laporte, G.; Walcher, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
The global behaviour of the normal function associated with van Geemen's family of lines on the mirror quintic is studied. Based on the associated inhomogeneous Picard-Fuchs equation, the series expansions around large complex structure, conifold, and around the open string discriminant are obtained. The monodromies are explicitly calculated from this data and checked to be integral. The limiting value of the normal function at large complex structure is an irrational number expressible in terms of the di-logarithm.